La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Journeys of Attachments, Trajectories of (Mis)fitting: Musicking in Deaf Communities in Montreal - Grenier, Line; Leduc, Véro (Troubling Inheritances: Memory, Music, and Aging, 2022)
This book provides an interdisciplinary focus on music, memory, and ageing by examining how they intersect outside of a formal therapeutic context or framework and by offering a counter-narrative to age as decline. It contributes to the development of qualitative research methodologies by utilizing and reflecting on methods for studying music, memory, and ageing across diverse and interconnected contexts. Using the notion of inheritance to trouble its core themes of music, memory, ageing, and methodology, it examines different ways in which the concept of inheritance is understood but also how it commonly refers to the practice of passing on, and the connections this establishes across time and space. It confronts the ageist discourses that associate popular music predominantly with youth and that focus narrowly, and almost exclusively, on music's therapeutic function for older adults. By presenting research which examines various intersections of music and ageing outside of a therapeutic context or framework, the book brings a much-needed intervention.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.